The infrastructure of the tourist market is the main tool for the development of the tourist business: classification and basics - Khassenkhanov, N.B.; Zhartay, Zh.M.; Nurgabdeshov А.М.; Petrova, M.M. (BUKETOV BUSINESS REVIEW, 2023)
Object: the object of the study is infrastructure, which is the main tool for the development of tourism business, including the main enterprises of accommodation, transportation. Methods: the method of analytical analysis is applied. The methods of classification and differentiation of the analysis of the structure of the object were used as a research method. Based on the method of classification and differentiation, it is possible to assess the state of the country’s tourist infrastructure. Findings: to implement optimal measures aimed at improving the level of service and capacity of infrastructure facilities on the basis of comprehensive improvement of tourism business infrastructure, continuous, optimal improvement and development of its elements, creating favorable investment conditions, improving the level of service and competitiveness of business representatives, eliminating district and local barriers, effective use of tourist facilities of the country improving effective management of systemic tourist complex as a regional, and private structures.